Genome-wide association studies identify four ER negative-specific breast cancer risk loci - Garcia-Closas, Montserrat; Chang-Claude, Jenny; Burwinkel, Barbara; Brenner, Hermann; Hamann, Ute; Marmé, Frederik; Schneeweiss, Andreas; Sohn, Christof; Müller, Heiko; Arndt, Volker; Hein, Rebecca; Kaaks, Rudolf; et al. (Nature genetics, 2013)
Montserrat Garcia-Closas and colleagues report a meta-analysis of three genome-wide association studies for estrogen receptor (ER)-negative breast cancer, including 4,193 ER-negative breast cancer cases and 35,194 controls, with replication using the iCOGS custom genotyping array in 40 studies, including 6,514 cases and 41,455 controls. They identify four loci associated with ER-negative but not ER-positive breast cancer.